De la musique à la lutte armée, de 1968 à Action directe : entretien avec Jean-Marc Rouillan - Luis Velasco-Pufleau (Transposition)
Jean-Marc Rouillan is one of the founding members of Action directe (1977–1987). In this interview, he talks about the connection between his musical practices and his political activism since the May 1968 events in France, the role of music and sound in the armed struggle of Action directe, and the place he attributes to music in the history of political struggles.